Taxogenomic and Metabolic Insights into Marinobacterium ramblicola sp. nov., a New Slightly Halophilic Bacterium Isolated from Rambla Salada, Murcia - Ana Durán-Viseras; David J. Castro; José Carlos Reina; Victoria Béjar; Fernando Martínez-Checa (Microorganisms, 2021)
A Gram-negative, motile, rod-shaped bacteria, designated D7T, was isolated by using the dilution-to-extinction method, from a soil sample taken from Rambla Salada (Murcia, Spain). Growth of strain D7T was observed at 15–40 °C (optimum, 37 °C), pH 5–9 (optimum, 7) and 0–7.5% (w/v) NaCl (optimum, 3%). It is facultatively anaerobic. Phylogenetic analysis based on 16S rRNA gene sequence showed it belongs to the genus Marinobacterium. The in silico DDH and ANI against closest Marinobacterium relatives support its placement as a new species within this genus. The major fatty acids of strain D7T were C16:0, summed feature 3 (C16:1 ω7c/C16:1 ω6c) and summed feature 8 (C18:1 ω7c/C18:1 ω6c). The polar lipid profile consists of phosphatidylethanolamine, phosphatidylglycerol and two uncharacterized lipids. Ubiquinone 8 was the unique isoprenoid quinone detected. The DNA G + C content was 59.2 mol%. On the basis of the phylogenetic, phenotypic, chemotaxonomic and genomic characterization, strain D7T (= CECT 9818T = LMG 31312T) represents a novel species of the genus Marinobacterium for which the name Marinobacterium ramblicola sp. nov. is proposed. Genome-based metabolic reconstructions of strain D7T suggested a heterotrophic and chemolitotrophic lifestyle, as well as the capacity to biosynthetize and catabolize compatible solutes, and to degrade hydrocarbon aromatic compounds.